Multimodal Performance and Interaction in Focus Groups - Gilbert, Kristin Enola; Matoesian, Gregory (Discourse Approaches to Politics, Society and Culture, 2021)
Focus group interviews have seen explosive growth in recent years. They provide evaluations of social science, educational, and marketing projects by soliciting opinions from a number of participants on a given topic. However, there is more to the focus group than soliciting mere opinions. Moving beyond a narrow preoccupation with topic talk, Gilbert and Matoesian take a novel direction to focus group analysis. They address how multimodal resources - the integration of speech, gesture, gaze, and posture - orchestrate communal relations and professional identities, linking macro orders of space-time to microcosmic action in a focus group evaluation of community policing training. They conceptualize assessment as an evaluation ritual, a sociocultural reaffirmation of collective identity and symbolic maintenance of professional boundary enacted in aesthetically patterned oratory. In the wake of social unrest and citizen disillusionment with policing practice, Gilbert and Matoesian argue that processes of multimodal interaction provide a critical direction for focus group evaluation of police reforms. Their book will be of interest to researchers who study focus group interviews, gesture, language and culture, and policing reform.